EPCO-21. STING PROMOTER EPIGENETIC SILENCING IN GLIOBLASTOMA. (9th November 2020) - Low, Justin; Bowie, Michelle; Chandramohan, Vidya; Fuller, Rebecca; Muscat, Andrea; Brown, Michael; Hariharan, Seethalakshmi; Hostettler, Janell; Briley, Aaron; Danehower, Sarah; Baker, Ali; Wong, Nick; et al.
Abstract: The Stimulator of interferon genes (STING) protein is a critical component of the innate immune response to pathogenic and cytosolic self DNA. The importance of STING signalling has recently been demonstrated in a number of tumor types, including glioblastoma (GBM), and its activation through STING agonism is a promising antitumor therapeutic avenue. Recent studies have shown a loss of STING expression in cancer and an overall dysregulation of the CGAS/STING pathway. A potential mechanism of STING silencing is the methylation of its promoter. Using bulk methylation array data from patient samples, we explore epigenetic control of the TMEM173 gene that encodes STING. We find that the STING promoter is highly methylated in glioblastoma and that STING RNA expression is correspondingly low. Methylation data from normal brain and non-cancer cerebral diseases reveal a consistent pattern of STING promoter hypermethylation in these diverse states. The degree of bulk STING methylation in GBM samples inversely correlates with tumor purity and markers of immune infiltration. Single-cell transcriptome sequencing reveals that STING is expressed specifically in immune cells and endothelial cells, but not glioma cells. Collectively these results suggest that STING signalling is disrupted in GBM, that STING is epigenetically silenced by DNA methylation in the tumor, and that STING expression in bulk GBM tumor samples arises from infiltrating immune cells in the tumor microenvironment. Therapeutic approaches stimulating the innate STING signalling pathway are therefore likely to be effective on infiltrating immune cells rather than tumor cells themselves. This work motivates further study into mechanisms of STING activation in the broader GBM tumor microenvironment.